CORRUPTION - SAFETY ISLAM IN THE UNITED STATES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article highlights how much corruption is a social phenomenon for the society, the dangers of unheard of each state, and the moral threat of evil.